MEMBANGUN SIKAP TERBUKA ORANG MUDA KATOLIK DALAM BERDIALOG DENGAN SESAMA YANG BERBEDA KEYAKINAN MELALUI KATEKESE SAKRAMEN PENGUATAN - Gonzaga, Yohannes Gonzales; Dadi, Kanisius Komsiah (CREDENDUM: Jurnal Pendidikan Agama, 2023)
To spread the good news, young people must demonstrate their identity as followers of Christ. This requires maturity, but obstacles to building maturity in young people exist, often due to their selfish attitudes. This attitude can hinder their ability to engage in dialogue with those holding different beliefs. Therefore, it is essential to provide coaching for young people to cultivate an open attitude in dialogue. With an open attitude, young people can develop the potential to establish cooperative relationships with people of different faiths. This research seeks insights into the Church's perspectives on fostering an open attitude in dialogue. The author relies on library resources to conduct this research, primarily focusing on the book "Religious Dialogue in the View of the Catholic Church." From this research, the author identifies the key values necessary to foster an open attitude in dialogue, which include honesty, sincerity, humility, and self-control. These four aspects will serve as the themes for the sacrament of confirmation catechesis activity program.